Case Report: Giant insulinoma, a very rare tumor causing hypoglycemia - Tarris, Georges; Rouland, Alexia; Guillen, Kévin; Loffroy, Romaric; Lariotte, Anne-Cécile; Rat, Patrick; Bouillet, Benjamin; Andrianiaina, Haingo; Petit, Jean-Michel; Martin, Laurent (Frontiers in Endocrinology, 2023)
Insulinomas, with an incidence of 4 cases per million individuals per year, remain amongst the most frequent functional neuroendocrine tumors. With a usual diameter estimated around 3 cmThe usual diameter of insulinomas usually remains under 3 cm of major axis. However, , the diagnosis of giant insulinoma remain therefore 44 exceptional cases of “giant insulinomas”, have been reported, with a total of 44 reported cases worldwide, generally exceeding 9 cm in major axis. In this article, we report the case of a 38-year-old woman whom suffered from chronic hypoglycemia despite treatment with diazoxide. Abdominal CT-scan revealed a 88 x 73 mm mass located at the tail of the pancreas. Following surgical excision, histopathological analysis confirmed G1 neuroendocrine tumor, with focal cytoplasmic expression of insulin in tumor cells. After a 16-month follow-up period, the patient didn’t address any specific complaint, and no disease recurrence and/or metastasis were observed. A 68Ga-DOTATATE-PET scan was performed 6 months after surgery, which came back normal. Genetic evaluation has not been performed in our Thepatient. The physiopathology of giant insulinomas remain unexplained, however with possible relationship with type 1 multiple endocrine neoplasia, sporadic somatic YY1 mutations and possible transformation of bulky non-functional pancreatic neuroendocrine tumors to a functional phenotype, with slow insulin secretion. While giant insulinomas remain rare in the literature, multicentric genetic analysis of tumor samples might reveal unique features of this rare subtype of neuroendocrine pancreatic tumors. Insulinomas of large size tend to have greater malignancy and higher rates of invasiveness. Careful follow-up, especially for liver and lymph node metastases, must be performed using functional imaging techniques to avoid disease relapse.